A Compartment-Based Mathematical Model for Studying Convective Aerosol Transport in Newborns Receiving Nebulized Drugs during Noninvasive Respiratory Support - Francesco Tarantini; Ilaria Milesi; Xabier Murgia; Federico Bianco; Raffaele L. Dellacà (MDPI AG, 2020)
Nebulization could be a valuable solution to administer drugs to neonates receiving noninvasive respiratory support. Small and irregular tidal volumes and air leaks at the patient interface, which are specific characteristics of this patient population and are primarily responsible for the low doses delivered to the lung (DDL) found in this application, have not been thoroughly addressed in in vitro and in vivo studies for quantifying DDL. Therefore, we propose a compartment-based mathematical model able to describe convective aerosol transport mechanisms to complement the existing deposition models. Our model encompasses a mechanical ventilator, a nebulizer, and the patient; the model considers the gas flowing between compartments, including air leaks at the patient-ventilator interface. Aerosol particles are suspended in the gas flow and homogeneously distributed. The impact of breathing pattern variability, volume of the nebulizer, and leaks level on DDL is assessed in representative conditions. The main finding of this study is that convective mechanisms associated to air leaks and breathing patterns with tidal volumes smaller than the nebulizer dramatically reduce the DDL (up to 70%). This study provides a possible explanation to the inconsistent results of drug aerosolization in clinical studies and may provide guidance to improve nebulizer design and clinical procedures.